2005
DOI: 10.1590/s1415-47572005000200021
|View full text |Cite
|
Sign up to set email alerts
|

A Floricaula/Leafy gene homolog is preferentially expressed in developing female cones of the tropical pine Pinus caribaea var. caribaea

Abstract: In angiosperms, flower formation is controlled by meristem identity genes, one of which, FLORICAULA (FLO)/LEAFY (LFY), plays a central role. It is not known if the formation of reproductive organs of pre-angiosperm species is similarly regulated. Here, we report the cloning of a conifer (Pinus caribaea var. caribaea) FLO/LFY homolog, named PcLFY. This gene has a large C-terminal region of high similarity to angiosperm FLO/LFY orthologs and shorter regions of local similarity. In contrast to angiosperms, conife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 40 publications
0
15
0
3
Order By: Relevance
“…LEAFY has been identified primarily with the specification of floral meristems in angiosperms, since loss-of-function alleles result in a partial loss of floral meristem identity and gain-of-function alleles cause inflorescence meristems to differentiate as floral meristems (Coen et al 1990;Weigel et al 1992;Weigel and Nilsson 1995). Thus, in angiosperms, LEAFY is thought to regulate the transition from vegetative growth to reproductive growth by directly or indirectly regulating the transcription of the ABC floral organ identity genes in angiosperms, and its expression pattern in gymnosperms is consistent with a similar role in these taxa (Lee et al 1997;Mouradov et al 1998a;Parcy et al 1998;Busch et al 1999;Frohlich and Parker 2000;Shindo et al 2001;Dornelas and Rodriguez 2005). In a limited phylogenetic context, LEAFY also regulates complexity of leaf development in some legumes (Hofer et al 1997).…”
Section: Leafymentioning
confidence: 94%
“…LEAFY has been identified primarily with the specification of floral meristems in angiosperms, since loss-of-function alleles result in a partial loss of floral meristem identity and gain-of-function alleles cause inflorescence meristems to differentiate as floral meristems (Coen et al 1990;Weigel et al 1992;Weigel and Nilsson 1995). Thus, in angiosperms, LEAFY is thought to regulate the transition from vegetative growth to reproductive growth by directly or indirectly regulating the transcription of the ABC floral organ identity genes in angiosperms, and its expression pattern in gymnosperms is consistent with a similar role in these taxa (Lee et al 1997;Mouradov et al 1998a;Parcy et al 1998;Busch et al 1999;Frohlich and Parker 2000;Shindo et al 2001;Dornelas and Rodriguez 2005). In a limited phylogenetic context, LEAFY also regulates complexity of leaf development in some legumes (Hofer et al 1997).…”
Section: Leafymentioning
confidence: 94%
“…Species of Pinus, Welwitschia, and Ginkgo contain two LEAFY homologues, and early data suggested that the angiosperm sequence was most similar to a male-specific gymnosperm copy. However, more recent data have shown that both gymnosperm genes can have mixed expression patterns (Dornelas and Rodriguez 2005;VĂĄzquez-Lobo et al 2007;Shindo et al 2010). Although further analysis has not supported the molecular genetic basis of the mostly male hypothesis, it is an important example of an early effort to use comparative developmental genetic data to inform evolutionary theory.…”
Section: The Origin Of the Flower Itselfmentioning
confidence: 99%
“…LFY ‐like genes are expressed in the developing GRS of all gymnosperms studied to date, consistent with a role for these genes in reproductive development (Mellerowicz et al ., ; Mouradov et al ., ; Shindo et al ., ; Carlsbecker et al ., ; Dornelas & Rodriguez, ; Guo et al ., ; Shiokawa et al ., ). A recent study in Norway spruce provides further support for a role of LFY‐like proteins in reproductive initiation: in the acrocona mutant, vegetative shoots can develop into female cones and this vegetative‐to‐reproductive transition correlates with an upregulation of LFY ‐like genes (Carlsbecker et al ., ).…”
Section: Introductionmentioning
confidence: 99%